Global Effects and Alarming Surprises of Russian Politics in the War Against Ukraine - Mausili, Dwi Rianisa; Arsat, Muhamad (Siddiq Institute, 2023)
The implicit war between Russia and Ukraine showcases Russia's interests and desire for dominance through the use of military power and intelligence, advanced weaponry across land, air, and sea domains. The research method employed is literature review. Primary data sources are online news and up-to-date YouTube videos related to the researched topic. Secondary data is gathered from credible books and journals. Data analysis involves data extraction, comprehensive reading, detailed analysis, and holistic-integrative description. The research findings indicate that war is a political product and has become a cultural institution to showcase Russia's national identity. The war is filled with political and economic intrigues, woven into Russia's interests as a superpower capable of rivaling the United States. The global effects of the Russia-Ukraine war will prompt other nations to enhance their alertness and military readiness, leading to increased arms purchases for strengthening their countries. It will also impact global oil prices, causing them to surge. Furthermore, there's the threat of ideological expansion if Russia gains control over the world.